Pemberdayaan da'i propesional di Kota Duri - hary anto (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2019)
Da'i as an example of society, which is demanded to be more qualified and able to interpret the da'wah messages to the community in accordance with the demands of the development of the people. The aspects that must be considered in building processional preachers are through the regeneration of preachers in the city of Duri. Based on observations of empowerment of professional da'i in the city of Duri has not been maximized, this is due to the finding that people are disappointed with the da'i who are in the city of Duri.